EFL Students’ Perceptions on Flipped Learning in an English Grammar Class - Yusmalinda Yusmalinda (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
The objective of this research was to investigate EFL students’ perceptions on the implementation of flipped learning. Employing a concurrent mixed method of data gathering techniques, this research was conducted in an English Literature Study Program of a private university in Padang, West Sumatera Province. The participants were fourth-semester students in an intermediate English grammar who were encouraged to actively participate in the class. The flipped instruction was implemented in four meetings. At the end of the sessions, a Google form questionnaire was handed out. Quantitative and qualitative data analysis found out that most students expressed positive perceptions on flipped learning, as indicated by its efficacy to facilitate preparation for offline sessions, making them more active, and completing grammar exercises better. Overall, flipped learning was acknowledged to be effective for English grammar in this study, despite few suggestions for the lecturers to assist them understanding material better.